2013
DOI: 10.5897/ajb2013.12313
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alcohol: oil molar ratio on the production of ethyl esters by enzymatic transesterification of canola oil

Abstract: The influence of alcohol:oil molar ratio on the canola oil transesterification reaction in solvent-free medium using free lipase from Thermomyces lanuginosus and Burkholderia cepacia was studied. The experiments conducted in batch reactor for 72 h at 37°C in cosolvent-free reaction system with ethanol addition in three steps showed great potential for ester production. The stepwise addition of ethanol allowed increasing yield throughout the total period of the reaction, even if the course has limited reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
6
0
3
Order By: Relevance
“…For the formation of DAGs, it was observed that the maximum formation was about 17% in the time of 96 H of reaction. The ethyl ester yield production increased after 72 H and the reduction of MAG formation is possibly caused by transesterification reaction reversibility and the system remained stable in the formation of MAG and ethyl esters (easier reaction due to the low complexity of molecules) [26,37, 38].…”
Section: Resultsmentioning
confidence: 99%
“…For the formation of DAGs, it was observed that the maximum formation was about 17% in the time of 96 H of reaction. The ethyl ester yield production increased after 72 H and the reduction of MAG formation is possibly caused by transesterification reaction reversibility and the system remained stable in the formation of MAG and ethyl esters (easier reaction due to the low complexity of molecules) [26,37, 38].…”
Section: Resultsmentioning
confidence: 99%
“…A condição de operação dos ensaios foi temperatura de 40 ºC, 1 g de biocatalisador e razão molar óleo: álcool de 9:1 com o tempo de reação monitorado de (0 -72 horas) com retiradas das amostras em tempos pré-determinados. Após o tempo de 72 horas o biocatalisador foi recuperado por filtração a vácuo, lavado com hexano, seco e logo em seguida adicionado a um meio reacional novo quando se deu inicio a uma nova batelada (Dantas et al, 2013 ).…”
Section: Reação De Transesterificaçãounclassified
“…A coluna foi operada a 40 ºC, com detecção UV-VIS a 210nm, com injeção de 20 μL e vazão de 1 mL.min-1. As curvas de calibração foram construídas a partir de diluições consecutivas das misturas de padrões de trioleina, 1,2-dioleina, 1-monooleina e oleato de etila e as quantificações foram realizadas somando as áreas relativas das espécies químicas comuns, submetidas à curva de calibração (Dantas et al, 2013 ).…”
Section: Análise Das Amostrasunclassified
“…Production of ethyl esters were monitored by HPLC. The enzymatic activity of ester production was defined as the amount of protein required to produce a micromole of ester in a minute [30]. A combined linear gradient with aqueous/organic and non-aqueous phases, adapted from Holcapek, M. et al [31] was used for HPLC [30,31].…”
Section: Transesterification Reactionmentioning
confidence: 99%